2021
DOI: 10.1002/alr.22744
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review to examine the relationship between objective and patient‐reported outcome measures in sinonasal disorders: recommendations for use in research and clinical practice

Abstract: Background Common sinonasal disorders include chronic rhinosinusitis (CRS), allergic rhinitis (AR), and a deviated nasal septum (DNS), which often coexist with shared common symptoms including nasal obstruction, olfactory dysfunction, and rhinorrhea. Various objective outcome measures and patient‐reported outcome measures (PROMs) are used to assess disease severity; however, there is limited evidence in the literature on the correlation between them. This systematic review aims to examine the relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 98 publications
(256 reference statements)
1
36
1
Order By: Relevance
“…Even though it is well-known that self-reported OD poorly correlates with olfactory tests [ 19 ] and PROMs could be unreliable when used to assess smell recovery in the long-term [ 9 ], they remain of value given their good discriminative ability [ 20 ]. Considering it would be almost impossible to assess olfaction using Sniffin’ Stick evaluation (average time 30–40 min per test), an accurate screening tool becomes crucial and, in this regard, PROMs play an important role.…”
Section: Discussionmentioning
confidence: 99%
“…Even though it is well-known that self-reported OD poorly correlates with olfactory tests [ 19 ] and PROMs could be unreliable when used to assess smell recovery in the long-term [ 9 ], they remain of value given their good discriminative ability [ 20 ]. Considering it would be almost impossible to assess olfaction using Sniffin’ Stick evaluation (average time 30–40 min per test), an accurate screening tool becomes crucial and, in this regard, PROMs play an important role.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have assessed correlations between PNIF and rhinitis symptom scores to this point, with some reporting correlations with nasal obstruction on VAS 12,55,56 and others reporting weak correlations with PROMs or TNSS. 57,58 Ultimately, the use of objective parameters can complement clinical evaluation elicited from patients’ perspectives on their disease impact, but more accurate physiologic measures are needed.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of relationships between other clinical outcomes and PROMs might be explained by several factors. First, it has been suggested that objective outcome measurements often focus on one physiological aspect, whereas PROMs are multifactorial [ 25 ]. Second, school-aged children with congenital anomalies tend to overestimate their performance, a phenomenon known as superiority bias [ 26 ].…”
Section: Discussionmentioning
confidence: 99%